Media and social inequality : innovations in community structure research - Pollock, John Crothers (London : Routledge, 2013)
'This text is among the first to systematically explore the impact of community inequality on reporting political and social change. Although most journalism scholars are still fascinated by the impact of media on society,'Media and Social Inequality' explores the reverse perspective: the impact of society on media'--P. [i]
Includes bibliographical references and index.
Keywords: Journalism -- Social aspects; Equality; Mass media -- Social aspects